Miseria della critica. Spengler redivivo - Cacciatore, Fortunato Maria (FedOA - Federico II University Press, 2023)
A spectral and haunting figure, Oswald Spengler, with his main work (The Decline of the West) reappears on the scene every time the present is experienced as a moment of crisis or political, ideological, cultural transition. Even in our own time, there are references, researches, and articles that, although in different ways, all seem to be connected by a worried regard for his diagnoses. In the two parts of this study, is made an attempt to show, however, why Spengler cannot be evoked (or dismissed) as the anti-West. Rather, it is a matter of pointing out how the mimetic blurring with the positions of the alleged prophet of doom, in the name of the West's self-love and its exceptionalism, risks confirming the prognosis of the decline, testifying to the misery, or impotence, of the critique aimed at opposing its fulfilment.